Risk Analysis of Economic and Physical Availability in Food Emergency in the Czech Republic - Eva LUKÁŠKOVÁ; Kateřina PITROVÁ; Zdeněk MÁLEK; Helena VELICHOVÁ (Communications of International Proceedings, 2021)
The article focuses on the issue of economic and physical availability of food in the Czech Republic, especially with regard to the declaration of a state of emergency. The issue has become very topical, especially in connection with a long-lasting emergency, which was declared due to the epidemic of COVID-19. The risks of economic and physical availability of food are evaluated through risk analysis methods and are further discussed and in the end a possible methodology of the procedure for food safety risk assessment is proposed. The aim of this work is to use risk analyses to evaluate the level of economic and physical access to food in times of emergency. We want to find out how our company is doing during an unprecedented experience with a situation that has amazed the whole world. The risk assessment according to physical availability will be based on both the food self-sufficiency of the Czech Republic and the availability of food as such. When assessing the availability of food, it is necessary to know the overall availability of food in retail chains and specialized food stores. The food self-sufficiency of citizens must also be considered when assessing the availability of food, whether they are able to grow food themselves, such as potatoes or fruit and vegetables, and in what quantities. The detailed elaboration of primary data is not the most important here in terms of the possible scope of the text, they were used to process analyses that answer the basic research question.
Keywords: Economic Availability of Food; Physical Availability of Food; State of Emergency; Risk Analysis.